The importance of singing in the liturgical celebration (2020)
Since the early Church has been observed the role played by music in the development of the Liturgy and the present text gives an account of its fundamental role, recognizing its contribution to live the moment of the Liturgy in a fuller way, since its function is to help unite the prayers of a people who cry out to their Lord. This important task is not only of the musician, but also of the priest and the faithful who must maintain and preserve the great treasure of liturgical music in the Church. Aspects such as the enculturation of the gospel and the understanding of the different cultural elements will be necessary for the present reflection.